PENGEMBANGAN LKPD BERBASIS SAINTIFIK PADA POKOK BAHASAN BANGUN RUANG SISI DATAR - Toat Raharjo; Yohanes; Awatif (Pendidikan Matematika | STKIP YM Bangko, 2022)
This research model uses a 4-D model which consists of four stages, namely: the definition stage (Devine), the design stage (Design), the development stage (Develop) and the dissemination stage (Disseminate). LKPD which has been validated by five experts. Validity is seen from the results of the validation sheet, while practicality is seen from the practicality questionnaire sheet of student responses, while the effectiveness of learning outcomes and student learning activities. The results of the analysis at the validation stage showed that the average score of the validation results from the material experts was 4.33, the validation from the linguists was 4.60 and the validation from the media experts was 4.94, so the results of all validations obtained an averageof 4.62 with very valid criteria. The results of the practicality questionnaire analysis show that the practicality of scientific-based worksheets produced is practical with a percentage of 96.70% and the percentage of completeness of classical learning outcomes of 78.6%. Based on the results of the study, it was found that the LKPD developed was valid, practical, and effective